Wanda's First Day - Sperring, Mark. (New York Scholastic Inc, 2004)
Wanda is a young witch who is off to her first day at school. But when she arrives, she notices that something is not right. All of her classmates have wands instead of brooms.
K - 2
Keywords: Witches - Fiction; School stories - Fiction; First day of school